(untitled) (Bangladesh Journal of Medical Biochemistry, 2013)
The aim of this study was to evaluate the serum level of total cholesterol, triglycerides (TG), low density lipoproteins (LDL) and high density lipoproteins, (HDL) in chronic obstructive pulmonary disease (COPD) patients admitted in National Institute of Disease of Chest and Hospital, Mohakhali, Dhaka during. January 2009 to January 2010. Twenty two patients with COPD and 22 healthy controls were included in this study. Total cholesterol, HDL and TG levels were determined with ILAB 1800 Chemistry Analyzer using ILAB test Reagents. LDL concentration was calculated using the Friedewald Equation. The mean level of TG was 150.04±29.66 mg/dl and 126.14±13.28 in COPD patients and healthy control, respectively. A statistically significant difference was found between the two groups (p<0.001). The mean level of TC was 181.83±20.11 mg/dl and 176.28±15.35 mg/dl in COPD patients and healthy control respectively (p<0.001). LDL level mean value was 116.12±14.26 mg/dl and 108.95±10.39 in COPD patients and control respectively (p<0.001). The mean value of HDL showed 38.79±2.4 in COPD patients and 39.014±1.56 in control. A statistically significance was also found between the two groups (p<0.001). Our results showed that the values of TC, TG, LDL were higher than healthy control that is highly significant statistically. On the other hand, the was significantly decreased HDL level compared with controls. DOI: http://dx.doi.org/10.3329/bjmb.v3i2.13810 Bangladesh J Med Biochem 2010; 3(2): 42-45